TO BE OR NOT TO BE CHARLIE: TWITTER HASHTAGS AS A DISCOURSE AND COUNTER-DISCOURSE IN THE AFTERMATH OF THE 2015 CHARLIE HEBDO SHOOTING IN FRANCE - Giglietto, Fabio; Lee, Yenn (AoIR Selected Papers of Internet Research, 2015)
Following a shooting attack by two self-proclaimed Islamist gunmen at the offices of French satirical weekly Charlie Hebdo on 7th January 2015, there emerged the hashtag #JeSuisCharlie [I am Charlie] on Twitter as an expression of condolences for the victims, solidarity, and support for the magazine’s right to free speech. By 9th January, the hashtag was used over five million times, making it one of the most popular topics in the platform’s history. However, there too emerged #JeNeSuisPasCharlie [I am not Charlie], almost simultaneously and explicitly countering the former, affirmative hashtag. Since the former hashtag entailed a tragedy of twelve deaths and support for the universal values of freedom of expression, #JeNeSuisPasCharlie carried the inherent risk of being viewed as opposing accepted social norms. Despite the risk, the negative hashtag was used more than 74,000 times over the next few days since 7th January. Against this backdrop, we set out to achieve an in-depth understanding of what was going on under that hashtag.